Accountability of service providers: Contributions of consumer protection law - Chadah, Sapna (2006)
The nee3d of accountability stems from the ideal that the institutions of public governance are the repositories of public power and public power in turn is the trust or faith of the people. Therefore, public purpose requires, public interest needs and public good demands that exercise of public power must be subjected to the benefit of the society as a whole. There is yet another dominant reason for enhancing accountability in public domain that power without liability of accountability is tyranny. It may also be added that public power is always linked with responsibility. Power without responsibility is against the norms of democracy and the rule of law ideals. - Reproduced.
Keywords: Accountability; Consumer protection